Impact of unilateral stroke on right hemisphere superiority in executive control. (8th January 2021) - Russell-Giller, Shira; Wu, Tingting; Spagna, Alfredo; Dhamoon, Mandip; Hao, Qing; Fan, Jin
Abstract: In our previous study, we have demonstrated a right hemisphere superiority in executive control of attention, with the right hemisphere being more efficient in dealing with conflict for stimuli presented in the left visual field. However, the unique and synergetic contribution of the two hemispheres to this superiority effect is still elusive. Here, using the lateralized attention network test, we compared the flanker conflict effect for stimuli presented in the left and right visual fields in patients with an ischemic stroke in the right or left hemisphere as the unilateral lesion groups and in patients with a transient ischemic attack without an acute infarction as the control group. In contrast to the transient ischemic attack group, which demonstrated a right hemisphere superiority in conflict processing, there was no evidence for such an effect in both unilateral stroke groups. These results can be explained by our model proposing that there is bilateral hemispheric involvement for conflict processing for information received from the left visual field and unilateral hemispheric involvement for conflict processing for information received from the right visual field, resulting in more efficient processing for the left visual field, i.e., the right hemisphere superiority effect. When there is damage to either hemisphere, the responsibility of conflict processing will largely fall on the intact hemisphere, eliminating the right hemisphere superiority effect. Highlights: We examined brain mechanisms of right hemisphere superiority of executive control. Unilateral stroke patients and controls completed the lateralized attention network test. Right hemisphere superiority was dampened in both left and right hemisphere stroke patients. Right hemisphere superiority of executive control is supported by the two hemispheres.